Tax Morale in Australia: What Shapes it and Has it Changed over Time? - Benno Torgler; Kristina Murphy (Center for Research in Economics, Management and the Arts (CREMA), 2004)
Why citizens pay their taxes voluntarily is an important question for tax administrations worldwide. Some believe it is because taxpayers are deterred from tax evasion out of a fear of being caught or penalised. Others, in contrast, suggest that factors such as the level of tax morale one has (i.e., the intrinsic motivation one has to pay their tax) affects compliance behaviour. While there have been numerous empirical studies published that have explored the role of deterrence on tax compliance behaviour, very few studies have explored the concept of tax morale in any detail. This study therefore attempts to rectify this gap in the literature. If tax morale is important in determining compliance behaviour, as several researchers have suggested, then it is also important to understand what might affect one's level of tax morale. The specific aim of this paper will be to identify factors that shape or have an impact on tax morale. Using data collected from the Australian wave of the 1981 and 1995 World Values Survey, this study will demonstrate that factors such as trust and moral beliefs play an important role in shaping tax morale in Australia. Further, it will be shown that tax morale has increased significantly in Australia since the early 1980s, and that it has done so at a faster rate than many other OECD countries. Possible explanations for this increase will be discussed.
Keywords: H26; H73; 330; Tax Morale; Tax Compliance; Tax Evasion; Australia